Surface Parameter Bias Disturbance in Radar Backscattering From Bare Soil Surfaces - Wang, Zhihua; Yang, Ying; Zeng, Jiangyuan; Chen, Kun-Shan (IEEE transactions on geoscience and remote sensing, 2024)
Surface parameters (roughness and soil permittivity) are crucial for characterizing backscattering from bare soil. However, the estimation of roughness parameters (root-mean-square (rms) height and correlation length) depends on the sample surface size. The conversion between dielectric constant and soil moisture is disturbed by the dielectric model. These estimation biases significantly compromise the reliability of backscattering coefficients derived from analytic modeling, numerical simulations, and experimental measurements. In this study, we illustrate the statistical relationship between sample surface size and estimation bias of surface roughness at varied accuracy levels. To quantify the estimation bias of surface roughness with sample surface size and the estimation bias of soil permittivity, we analyze the propagation from the estimation bias of surface parameters to the backscattering coefficient error by the advanced integral equation model (AIEM) model. By comparing it with measurement data, we quantitatively confirm the impact of roughness parameter estimation bias. Ultimately, quantifying the backscattering coefficient error as a function of sample surface size and incident angle allows for selecting the optimal sample surface sizes suitable for L-band synthetic aperture radar (SAR) simulation and soil moisture retrieval, along with their applicability over various incident angles. This study suggests sample surface sizes for estimating roughness parameters and backscattering coefficients at various levels of accuracy.